THINK PAIR SHARE METHOD IN IMPROVING ABILITY TO MEMORIZE TASHRIF ISTILAHI IN LEARNING SHARAF FOR SANTRI DARUL MUTTAQIEN BOARDING SCHOOL - Rendi Al Khafidh; Eva Iryani; Muhammad Sobri (The Islamic Education and Multiculturalism Foundation, 2021)
Abstract: Darul Muttaqien Islamic boarding school is a boarding school located in the village of Pauh Menang. Darul Muttaqien Islamic boarding school teaches religious lessons, including Arabic. The research focuses on the think pair share method that will be used in the branch of science in Arabic, namely the learning sharaf. This method has been used by the Islamic boarding school to improve ability to memorize the term tashrif in the science of sharaf and researchers have also tried to use this method. This study aims to find out how the use of the think pair share method and the quality of the think pair share method in improving students' ability to memorize tashrif istilahi. In this study, researchers used qualitative data. Sources of data were obtained from learning sharaf’s teacher and students at the Darul Muttaqien Islamic boarding school. Data was collected using observation, interviews and documentation. The data analysis used is qualitative data analysis. The results showed that, 1) in the classroom using one-way learning, from teacher to student, Ustadz explained the whole thing and Santri listened to every material explained by the ustadz and used guidelines to make it easier to memorize and then repeat rote in the dormitory called taqrar. 2) some obstacles in memorizing the tashrif istilahi for the students, that is (a) because there are some differences between waazan and mauzun, (b) the activeness of students in learning, (c) there is a change in the letter i'lal, (d) the difficulty of remembering in memorizing , (e) lazy and sick students.